Stoicism : traditions and transformations. (Cambridge Univ Press, 2004)
How did Stoicism influence Western thought after Greek and Roman antiquity? Contributors for this volume include some of the leading international scholars of Stoicism as well as experts in later periods of philosophy. They trace the impact of Stoicism from late antiquity through the medieval and modern periods.